ByzRev 07.2025.012: Emmanuel S. Moutafov, The Chora Monastery of Constantinople: (Elements in the History of Constantinople). Cambridge: Cambridge University Press 2024. - Semoglou, Athanasios (The Byzantine Review, 2025)
Emmanuel S. Moutafov, The Chora Monastery of Constantinople (Elements in the History of Constantinople). Cambridge: Cambridge University Press 2024. 96 pp. – ISBN 978-1-108-93113-7